Community Based Conservation: Redefining Boundaries (Journal of Forest and Livelihood, 2016)
Conservation and management of biodiversity is complex and a localized phenomenon in the Terai Arc Landscape (TAL) which is inhabited by 7.4 million people out of which 25 per cent are still below the poverty line. There is significant interaction between the human and natural resources with diverse values of biodiversity and ecosystem services to the local populations. The implications of variations in terms of dependence on natural resources are that conservation and management strategies broadly vary across the landscape. Success and failures of conservation strategy/approach cannot commonly be extrapolated across this diverse landscape. While many projects in TAL have failed, some have succeeded too and is shaped by multiple factors including the type and level of human interactions with biodiversity. This review article provides reflections on experiences of decades of Community Based Conservation (CBC) in Nepal with a specific focus on Chitwan National Park and its buffer zone located in TAL. CBC confronts newer challenges and issues pertaining to inadequate mechanisms to address communities beyond buffer zones in a scenario where conservation needs to move beyond the conventional boundaries of parks and buffer zones, equitable benefit sharing, inequalities within communities, increasing human-wildlife conflicts, ecotourism, nexus of poverty-livelihood and conservation. However, CBC offers greater potentials and opportunities for greater local community engagement in a changing context to reconcile local development with conservation.